Preparation and characterization of ordered intermetallic platinum phases for electrocatalytic applications - Pinto, L. M. C. [UNESP]; Silva, E. R. [UNESP]; Caram, R.; Tremiliosi-Filho, G.; Angelo, A. C. D. [UNESP] (Elsevier B.V., 2008)
Ordered intermetallic phases of Pt with several transition metals have been prepared and their electrocatalytic properties studied. In light of these tests it is proposed that these catalysts could be used as electrodes in fuel cells, as they combine an excellent capacity to adsorb organic fuels at the Pt sites with low susceptibility to being poisoned by intermediates and reaction products at the transition-metal sites. An experimental procedure used to obtain the four intermetallic phases Pt-M (M = Mn, Pb, Sb and Sn) is described. The phases thus produced were characterized by X-ray diffraction, scanning electron microscopy with surface analysis by energy-dispersive X-ray spectrometry, scanning tunneling microscopy and X-ray photoelectron spectroscopy. The data thus obtained support the conclusion that the method described here is highly effective for the preparation of Pt-M phases featuring a range of structural and electronic modifications that will allow a useful relation to be established between their physicochemical properties and predicted electrocatalytic activity. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: intermetallics; miscellaneous; crystallography; electronic structure of metals and alloys; melting; catalysis